Sobre a Transmissão Sexual do Vírus da Hepatite C (HCV) - Stabnov, Ivan Márcio; Garbes-Netto, Pedro (Brazilian Journal of Sexually Transmitted Diseases, 1995)
The authors presenta retrospective study about sexual transmission of HCV, poiting the main features toward this form of spread with its counterparts. An ethiologic and epidemiologic review is done, enhancing the secual pattern to maintain the mfection in nature, specially in a high endemicity environment and prevention methods.